Affinity-based enrichment strategies to assay methyl-CpG binding activity and DNA methylation in early Xenopus embryos - Bogdanović, Ozren (BioMed Central, 2011)
BACKGROUND: DNA methylation is a widespread epigenetic modification in vertebrate genomes. Genomic sites of DNA methylation can be bound by methyl-CpG-binding domain proteins (MBDs) and specific zinc finger proteins, which can recruit co-repressor complexes to silence transcription on targeted loci. The binding to methylated DNA may be regulated by post-translational MBD modifications. FINDINGS: A methylated DNA affinity precipitation method was implemented to assay binding of proteins to methylated DNA. Endogenous MeCP2 and MBD3 were precipitated from Xenopus oocyte extracts and conditions for methylation-specific binding were optimized. For a reverse experiment, DNA methylation in early Xenopus embryos was assessed by MBD affinity capture. CONCLUSIONS: A methylated DNA affinity resin can be applied to probe for MBD activity in extracts. This assay has a broad application potential as it can be coupled to downstream procedures such as western blotting, fluorimetric HDAC assays and quantitative mass spectrometry. Methylated DNA affinity capture by methyl-CpG binding proteins produces fractions highly enriched for methylated DNA, suitable for coupling to next generation sequencing technologies. The two enrichment strategies allow probing of methyl-CpG protein interactions in early vertebrate oocytes and embryos.